南極昭和基地におけるIoT 活用に向けた920 MHz 帯小電力通信試験 - 岡田, 雅樹; オカダ, マサキ; 佐々木, 貴美; ササキ, タカミ; 加藤, 拓也; カトウ, タクヤ; 経沢, 正邦; ツネザワ, マサクニ; 古川, 浩史; フルカワ, ヒロシ; 大谷, 朋広; オオタニ, トモヒロ; et al. (国立極地研究所, 2021)
2017 年より国内での利用が始まった920 MHz 帯小電力無線システム用の電波を活用し，昭和基地における観測機器のデータ収集を始めとした基地インフラの監視を実現することを目的として，第61 次南極地域観測隊において東オングル島及びその周辺地域における920 MHz 帯電波の到達状況と既存の基地観測への影響を調査した．調査においてはLoRaマルチホップが可能な通信機器を製作し，隊員が携帯する送信装置から発信されるGPS の位置・時刻情報を，昭和基地基本観測棟の3 階階段手摺に設置したLoRa ゲートウェイで受信することで，各地における受信信号強度や信号対雑音比などのデータを収集した．越冬期間中6 回に及ぶ調査の結果，920 MHz 帯電波の特性から小電力にも関わらず広い範囲で電波の到達が確認され，将来の観測への応用及び，基地インフラの監視等IoT 活用への応用が期待できることが判明した． LoRa communication protocol using 920 MHz-band has been opened to the public for Internet of Things (IoT) application and a wide variety of telemeter usage since2017 in Japan. It is expected to be used for collection of scientific observations and monitoring data at Syowa Station. In JARE61, we have investigated the radio environment of the 920 MHz-band, and its possible impact on the ongoing scientific observations in Syowa Station．A member of the wintering team carries a handy transmitter in the nearby area of Syowa Station, East-ongul Island. The transmitter sends GPS location and time data to the receiver (LoRa gateway) located at the roof handrail of the observation building. Six surveys have been conducted, and we confirmed the reachability of the radio signal in and outside of the Syowa Station. The possibilities of the 920 MHz-band application have been suggested to use monitoring station infrastructure and scientific observations. departmental bulletin paper